(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
This study examines the Scientometrics appraisal of the Journal of Intellectual Property Rights (JIPR) for eight years from 2003-2010. This paper analyses the year wise distribution of articles and citations, authorship pattern, the degree of collaboration, the subjects covered and the length of the articles in the journal. The results indicate that the average number of contribution per issue is 6.46, the maximum number of contribution of article is by single author and patents as subject is covered with more number of articles. The maximum length of an article goes to 13.59 with the minimum of 6.75 pages. It is found that this is an important journal in the field of IPR, which every organization should procure and make it available to the users. Palavras-chave: Bibliometrics. Scientometrics. IPR. Patents. Copyright.NISCAIR. Link para o texto completo (PDF) http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/1162/2929